Implementasi Media Pembelajaran Ular Tangga Edukatif untuk Meningkatkan Motivasi dan Pemahaman Siswa SD Negeri Ngebung 1, Kecamatan Kalijambe, Sragen, Jawa Tengah - Mahardika, Adnan Gemma; Nurul Haslinda; Enggi Mudaya Ekowati; Shafia Fatinnisa; Anissa Alya Sofiani; Charunia Putri Banowati; Izzah Alma Maghfira; Choirunnisa Balqis Wangsa Putri; Meylinda Nurlatifah; Brigita Lidya Angelita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to describe the implementation of an educational snakes and ladders game as an innovative learning medium to enhance students’ motivation and understanding at SD Negeri Ngebung 1, Kalijambe District, Sragen, Central Java. The activity, initiated by the Community Service Program (KKN) Team 297 from Universitas Sebelas Maret, was conducted on July 23 as part of the program “Edu Fun: Education in Games”, aligning with the fourth goal of the Sustainable Development Goals (SDGs): Quality Education. The snakes and ladders game was modified so that each square contained educational questions or challenges related to school subjects, general knowledge, and character values. This interactive approach was designed to reduce classroom learning fatigue, foster critical thinking, and create an engaging learning atmosphere. The results of the implementation showed a high level of enthusiasm among students, who actively collaborated in groups to answer questions and complete challenges, with teachers also participating in facilitating the activity. This initiative demonstrates that incorporating educational games into classroom activities can serve as an effective strategy for enhancing both motivation and comprehension among elementary school students.